Response of molars and non-molars to a strict supragingival control in periodontal patients - Angst, Patrícia Daniela Melchiors; Piccinin, Flávia Benetti; Oppermann, Rui Vicente; Marcantonio, Rosemary Adriana Chierici [UNESP]; Gomes, Sabrina Carvalho (FapUNIFESP (SciELO), 2013)
The posterior position in the arches is one of the factors that underlies the poor prognosis of molar teeth (M). It is speculated that M do not benefit from the oral hygiene routine as well as non-molars (NM) do. This study evaluated the response of M and NM to supragingival control during a 6-month period in 25 smokers (S) and 25 never-smokers (NS) with moderate-to-severe periodontitis. One calibrated examiner assessed visible plaque (VPI) and gingival bleeding (GBI) indexes, periodontal probing depth (PPD), bleeding on probing (BOP), and clinical attachment loss (CAL) at days 0 (baseline), 30 and 180. At baseline, M showed significantly higher mean values of VPI (p = 0.017) and PPD (p < 0.001) compared with NM; CAL was also greater in M (p < 0.001) and was affected by smoking (p = 0.007). The reductions obtained for periodontal indicators at day 180 showed similar responses between M and NM. For CAL, M (NS 0.57 ± 0.50; S 0.67 ± 0.64) and NM (NS 0.38 ± 0.23; S 0.50 ± 0.33) reached an almost significant difference (p = 0.05). Smoking did not influence the response to treatment. Multilevel analysis revealed that, only for PDD reductions, the interaction between sites, teeth and patient was significant (p < 0.001). It was concluded that M benefit from an adequate regimen of supragingival biofilm control; therefore, supragingival condition should be considered in the prognosis of molar teeth.
Keywords: Dental scaling; Periodontitis; Smoking; Tooth; adult; biofilm; epidemiology; female; histology; human; male; methodology; middle aged; molar tooth; mouth hygiene; periodontal disease; periodontitis; preventive dentistry; time; tobacco; tooth; tooth plaque; treatment outcome; Adult; Biofilms; Dental Plaque; Dental Scaling; Epidemiologic Methods; Female; Humans; Male; Middle Aged; Molar; Oral Hygiene; Periodontal Attachment Loss; Time Factors; Tobacco; Treatment Outcome